The Effect of Digital Story Telling on Students' Reading Literacy to EFL Learners - Zuraini, Zuraini; Hayati, Rahmi; Meilinar, Fina; Marzuki, Marzuki (Yayasan Ilomata, 2024)
The aims of this research to investigate how digital storytelling influences reading literacy among students learning English as a foreign language (EFL). Reading literacy is a multifaceted skill that is crucial in both educational contexts and daily life, enabling individuals to interact effectively with the world around them. The problem of this research how does digital story telling influences students reading literacy. Digital story telling important for English language learning not only reading literacy but also could detail insights into student experiences and perceptions. The method of this research is qualitative research. Utilizing a descriptive case study design, the study employs qualitative methods, including observations and interviews, to gather data on student engagement and learning outcomes. The result of this research are students involved in digital story telling activities demonstrated a better understanding of texts, as they engaged more deeply with the material through the creative process of storytelling, students actively assessed and synthesized reading content, made connections between ideas, and critically evaluated story elements during collaborative discussions.